Pengaruh Brain Gym Terhadap Tingkat Konsentrasi Belajar Siswa di SDS Eben Haezer Family - Bunga Apriwati Sinaga; Sri Muharni; Utari Christya Wardhani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Concentration of learning in children is how children focus on doing or doing something until the job is done in a certain time. In some 6th grade children at Eben Haezer Family Elementary School have difficulty concentrating which causes a decrease in learning achievement due to the fact that children often play gadgets, experience low thinking levels such as memory disorders, and children have a history of illness since childhood so that teachers who also complain and are confused in improving and overcoming children who have difficulty concentrating when learning takes place. Brain gym is a collection of simple movements that aim to connect or unite the mind and body so that not only will facilitate the flow of blood and oxygen to the brain, but also movements that can stimulate the work and functioning of the brain optimally. This study was conducted to determine the effect of Brain Gym on the level of learning concentration in students at SDS Eben Haezer Family. This study is a quantitative research pre-Experimental approach one group pre-post test with a sample of 21 respondents with a total sampling technique. Analysis of the data in this study using the Wilcoxon test with the analysis test obtained the value of p value =0.000 (p<0.05) so that the conclusion of this study there is the influence of Brain Gym on the level of concentration of learning in students at SDS Eben Haezer Family.